THE ELABORATIVE PANORAMA OF PANORAMIC RADIOGRAPHY: AWARENESS AMONG BUDDING DENTISTs - Ravinder Singh,; Amit Aggarwal,; Deepak Gupta,; Rakashree Chakraborty,; Taruna Mahant,; Preeti Garg Mittal , (International Journal of Psychosocial Rehabilitation, 2020)
Background: Panoramic radiography is one of the most widely accepted and familiar extra-oral radiographic examination techniques and Increasing numbers of panoramic radiographs are been taken every year worldwide.  The faculty of dental colleges educates students about panoramic radiography. The purpose of this study was to assess the capability of undergraduate dental students whether they are able to interpret normal anatomical landmarks, technique errors or any pathology on panoramic radiographs. Material and Methods: A cross-sectional prospective study was done in which a self-rectified questionnaire that was divided under four headings was prepared by the faculty of oral medicine and radiology department to be filled by students who entered in their internship for the year 2019-20 and were examined. The data collected was statistically analyzed with pie charts and graphs. Results: The answers collected showed the correct answers with the average mean rate is 55% ± 5%. Interns performed well and correctly identified in errors and artifacts (65%- 81%), followed by the anatomical landmarks (56% - 62%), and followed by the basic principles (49%-63%). Mean of 43% students were able to rule out the pathological changes. Conclusion: The final outcome of dental education, the dentist, must be a competent clinician in all aspects of dentistry. Therefore to improve the ability of the practicing dentist to effectively use panoramic radiography, we should expand the curricular time devoted to panoramic radiography, both in the class and in the clinic.